Evaluation of Electronic Customer Relationship Management: The Critical Success Factors - Lin, Chad; Lin, K.; Huang, Y.; Kuo, W. (American Academy of Business, Cambridge, 2006)
Electronic customer relationship management (eCRM) is becoming increasingly important as organizations seek to deliver their services and information as well as to provide transactional facilities via online and wireless platforms, in additional to the more traditional means of communication channels. However, relatively little research has examined how organizations evaluate their eCRM systems. We take a multi-case study approach to: (1) develop an integrated framework to assist organizations in evaluating their eCRM; and (2) present factors and guidelines that can assist senior managers in implementing their eCRM so organizations can better manage their investment and improve their long term profitability. One important outcome of this research is the development of an integrated eCRM critical success factors (CSFs), benefits, costs, and risks framework which enables organizations to examine their relationships in the context of eCRM implementation. The framework provides some general guidelines for implementing eCRM which enables organizations to pay attention to the strategic alignment relationships between the four strategic components as well as to consider the possible benefits, costs, and risks which will arise from the CSFs of these strategic components.